Menuju pemuridan yang efektif bagi mahasiswa Sekolah Tinggi Teologi generasi Z - Winarsih Winarsih (Sekolah Tinggi Teologi SAPPI Ciranjang, 2022)
The results of the literature research show that in order to achieve effective discipleship, generation Z seminary students still need to go through a fundamental process in discipleship, namely the transformation of thoughts through the process of formation and reform. The process of transforming the mind can only occur if generation Z seminary students accept Christ as Savior, which will be followed by transformation in every part of their lives. The progressive transformation of generation Z seminary students will be able to fight the challenges of today's idolatry if environment of the generation Z seminary students is designed in such a way that they are continuously supported to live out their new identity as children of God, related to the Triune God and the body of Christ. Theological works through counseling and media digital are also needed to be used in making effective discipleship at seminary, especially for generation Z.